ADVERGAME FOR PURCHASE INTENTION VIA GAME AND BRAND ATTITUDES FROM ANTECEDENTS OF SYSTEM DESIGN, PSYCHOLOGICAL STATE, AND GAME CONTENT: INTERACTIVE ROLE OF BRAND FAMILIARITY. Issue 1 (2nd January 2022) - Hsiao, Wei-Hung; Lin, Yu-Hsiu; Wu, Ing-Long
ABSTRACT: Advergame is important as a new form of digital marketing and few studies have shown a complete model structure along with understanding the antecedents of online purchase intention. Based on the hierarchy of effective and relevant behavioral theories, we propose a research model with four components: consumer beliefs, advergame attitude, brand attitude, and purchase intention. The elaboration likelihood model (ELM) is used as a complementary lens to define three game beliefs: advergame design, psychological state, and advergame content. A comprehensive literature review is further classified to define their comprised elements. Brand familiarity is shown as a moderator for the link of advergame and brand attitude due to a connection to behavioral theories. Empirical study consists of an online survey of 477 consumers who had recent experience of advergame playing. Most variables for game beliefs, including game-brand fit, perceived interactivity, involvement, entertainment, and receptiveness, show significant, positive effects on advergame attitude. Besides, advergame attitude reports an important, direct link with purchase intention. Brand familiarity indicates importance as the moderator.